Hubungan Dukungan Keluarga dengan Paparan Pornografi pada Remaja - Desriati Devi; Yenni Sasmita; Fathimi Fathimi; T.Cut Lizam; Hardisal Hardisal (Jurnal Vokasi Keperawatan (JVK), 2023)
Adolescents are currently growing up in the digital era with the increase and development of internet technology which not only brings benefits, but also harms, one of which is exposure to sexual content, namely pornography. The increase of information and technology development constructs adolescents that are susceptible to the possibility of pornography exposure through accessibility such as social media and online games. Pornography is one of the negative impacts that can affect adolescent behavior, so it requires supervision. The role of parents is really needed by adolescents in providing sexual knowledge information and safe internet use, as well as support as an effort to prevent pornography exposure. This study aims to examine the relationship between family support and pornography exposure in adolescents. This descriptive correlative design used a cross sectional study. The population was all students in one of the State Junior high Schools in South Aceh Regency with a sample of 94 students. Data collection was carried out using questionnaires as a research instrument. Chi Square test was used in analyzing the data. The Results indicated that 66% of adolescents were exposed to pornography. The results of the analysis showed that there was a significant relationship of p=0.0001 (p<0.05) between family support and pornography exposure. Family support has a significant relationship with pornography exposure. It is expected that families and schools can increase support in monitoring and preventing adolescents from accessing pornography.